A Framework for Understanding the Intra-Islamist Conflict Between the AK Party and the Gülen Movement. (2nd January 2018) - Yavuz, M. Hakan
ABSTRACT: This article examines the circumstances shaping the evolution of the Gülen movement. Once considered a relatively liberal and pluralistic Islamic movement based in Turkey, the movement later succumbed to authoritarianism and illiberalism following its political alliance with the AK Party and their subsequent falling out. The paper opens with a brief overview of the historical context of the relationship between state and society in the Ottoman Empire and then examines the politicization of Islam as a movement of resistance against the modernizing reforms of the Kemalist state. The complex interplay of these factors culminated in the construction of a secular communalism in Turkey. The remainder of the paper focuses on the triangulated relationship among state, society, and religion, targeting the alliance and political struggles between the AK Party and the Gülen movement. The paper concludes that once legal and political checks and balances are removed, Islamic movements bend towards authoritarian tendencies seeking to monopolize or, at least, influence nearly every sphere of social and political life. After a decade-long experiment with Islamic movements in power, Turkey—increasingly authoritarian in character and socially fragmented—is experiencing the most serious institutional crisis in its history as a modern republic.